Diagnostic Accuracy of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration (EBUS-TBNA) in Real Life - Murthi, Mukunthan; Donna, Elio; Arias, Sixto; Villamizar, Nestor R.; Nguyen, Dao M.; Holt, Gregory E.; Mirsaeidi, Mehdi S. (Frontiers in Medicine, 2020)
Background: EBUS-TBNA is an integral tool in the diagnosis and staging of lung cancer and other diseases involving mediastinal lymphadenopathy. Most studies attesting to the performance of EBUS-TBNA are prospective analyses performed under strict protocols. The objective of our study was to compare the accuracy of EBUS-TBNA to surgery in diagnosing hilar and mediastinal pathologies in a tertiary hospital, staffed by pulmonologists with and without formal interventional pulmonary training. Methods We retrospectively analyzed subjects who underwent EBUS-TBNA followed by a confirmatory surgical procedure from January 2012 to December 2018. The primary outcome was to evaluate the accuracy of EBUS-TBNA in the diagnosis of all mediastinal disease. Secondary analyses determined the accuracy of EBUS-TBNA in cancer, NSCLC and non-malignant lesions individually. Results One hundred and forty-three subjects had an EBUS-TBNA procedure followed by surgery. EBUS-TBNA for all pathologies had an accuracy of 81.2% (CI 95% 73.8-87.4) and sensitivity of 55.1% (CI 95% 41.5-68.3). The accuracy and sensitivity of individual groups were: cancer (81.7%, 48.8%), NSCLC (84%, 48.3%) and non-malignancy (78.9%, 60%). The NSCLC group had 15 false negatives and 5 (33.3%) of them were due to non-sampling of EBUS accessible nodes. Missed sampling led to a change in the final staging in 8.6% of NSCLC subjects. Conclusion The accuracy of EBUS-TBNA across all groups was comparable to those reported previously. However, the sensitivity was comparatively lower. This was primarily due to the large number of EBUS-TBNA accessible lymph nodes that were not sampled. This data highlights the need for guidelines outlining the best sampling approach and lymph node selection.